Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Karyawan PT. Haji Maming Alma Batulicin - Muhammad Taher; Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
The purpose of this study was to test and find out whether there is an effect of workload and work stress on the performance of all employees in the company's work environment PT. Haji Maming Alma Batulicin. This study uses a survey method with a quantitative approach, while the population of this study are all employees who work at the company PT. Haji Maming Alma Batulicin which totaled 50 people. This study uses a total sampling technique or uses all employees as samples from the study. Data collection techniques in this study used a questionnaire with the results in the form of numbers and were analyzed using multiple linear regression. The results of this study indicate that the workload variable partially has a significant effect on employee performance, then work stress partially also has a significant effect on employee performance, and workload and work stress simultaneously have a significant effect on PT. Haji Maming Alma Batulicin